The Potency of Krokot (Portulaca oleracea) as Functional Food Ingredients - Daisy Irawan; Purwiyatno Hariyadi; Hanny Wijaya (Indonesian Food and Nutrition Progress, 2003)
Indonesia has many auxiliary plants that may have nutritional and or environmental benefits, so that it may increase the yield of the main crops. Krokot (Portulaca oleracea), one of the auxiliary plants, was traditionally consumed in many parts of the world for its delicacy and medicinal benefits. Our research indicated that krokot has high potency to improve the health status of the community. It has 5.4 mg/100 g of b-carotene, 22.2 mg/100 g of vitamin C, and significant amount of folic acid (0.2 mg/100 g). Krokot was traditionally used to treat scurvy, and various of infectious and skin diseases. Literature review revealed that krokot has essential .fatty acid, it also has antiniutagenic, and antimicrobial activity. Unfortunately, krokot is approaching extinction both physically and ethnobotanically because they are considered as useless plants or even weed. Our survey on 103 agricultural university students revealed that only 24% of the respondents knew krokot. Krokot is especially difficult to find in intensively cultivated area. Along with other indigenous vegetables, Portulaca oleracea is almost never served again in Indonesian cuisine. -Utilization of krokot as functional food ingredients might helps to conserve the plant as well as encouraging sustainable agriculture.